Risk Tolerance: Heuristic Bias Towards Investment Decision Making - Wahyu Febri Ramadhan Sudirman; Mohd Winario; Arif Mudi Priyatno; Zubaidah Assyifa (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: This study aims to examine how risk tolerance influences the role of overconfidence bias and availability bias in investment decision-making. Because of the complexities of the investment decision-making process, this study attempts to investigate psychological variables in the investment decision-making process. Design/Methods/Approach: This study used the Structural Equation Modeling Partial Least Squares (SEM-PLS) analytic approach using the SmartPLS 3 program and survey data provided online to stock investors, with a total of 303 samples obtained. The study applied CMB preventive techniques to decrease common method bias (CMB). Findings: The results indicate a positive and significant mediating role of risk tolerance on the effect of overconfidence bias and availability bias toward investment decision-making. Originality/Value: This research seeks to explore the process of making investment decisions by taking into account the psychological aspects of investors by using a more comprehensive Bounded rationality theory point of view. This study tested the mediation mechanism of risk tolerance in bridging the influence of heuristic bias on investment decision-making, which has not been explored much by previous studies. Practical/Policy implication: The findings can guide investors to consider how they make biased investment decisions and help investment managers assess the appropriate level of investment risk.